Community Perception on the Effect of Cultural Livelihoods on the Environment in Kogi State, Nigeria - G. O. Chukwurah, N. M. Aguome, M. O. Isimah, E. C. Enoguanbhor, N. E. Obi-Aso, N. U. Azani and O. C. Nnamani (Nature Environment and Pollution Technology)
This study examines the cultural livelihood of Kogi State and its effects on the environment. The study describes some of the cultural livelihood practices found in Kogi State, considering the contemporary condition of cultural livelihood and its effects on the environment. Secondary and primary data were employed, which include archives and internet search engines. Using a 4-stage sampling procedure, data were collected from a 120-person sample through an interview, field observation, a focus group discussion, and a questionnaire. Descriptive statistics using frequencies, percentages, and charts were used for the analyses. The results were compiled using the Statistical Package for Social Sciences (SPSS). Findings show that about 85% of the participants discovered crop farming, arable farming, weaving, blacksmithing, fishing, and festivals of harvest, such as the New Yam Festival, among others, as the predominant cultural livelihoods. The local farming implements were made of local materials, like stones and wood. They have indigenous crop production, protection, and harvest techniques. The farming tools were economical in terms of labor, affordability, and time savings in the subsistence farming system. The study discovered that cultural livelihoods are 4% very efficient and 56% on the verge of extinction. Analyses of the effect of cultural livelihood show that 78% have a high negative effect on the economic environment, 57% have a moderate negative effect on the social environment, 51% hurt the political environment, and 22% have a low negative effect on the political environment. The intervention of the various tiers of government with the cooperation of the various communities is needed for the provision of a conducive environment for the practice of cultural livelihood, particularly in the aspect of insecurity. Adequate provision of modern equipment, funding, and social welfare services is also recommended to enhance cultural livelihoods.